Taá¹awwur al-TarbÄ«yah al-IslÄmÄ«yah (Surau) fÄ« Minangkabau - Mulyani, Mulyani (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
The development of Islam in Minangkabau is inseparable from the development of Islamic education and broadcasting that took place in the surau-surau. Position surau in Minangkabau as important as the position in the context of the development of Islamic boarding schools in Java. As pesantren, surau a printer agent of the scholars responsible for transmitting the teachings of Islam and building societies to be the people who obey the above teachings.DOI:Â 10.15408/sdi.v4i1.790